Perjanjian Kredit dengan Jaminan Fidusia atas Kendaraan Bermotor di PT. BPR Artha Mutiara Kab. Semarang - Oktorio Hery Kusworo (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
People need about quick funds is very high nowadays. It is because of the inadequacy of their abilities to fulfill their daily needs. Because of that reason, people will be looking for an institute who can set aside credit funds. In this case, it refers to Bank Perkreditan Rakyat (BPR). BPR helps people by giving credit through easy and quick process. BPR credit also uses treaty, which is credit treaty. To make sure the debitors pay their debt, credit treaty is followed by Agunan (guarantee). Guarantee that mostly used in BPR is for motor vehicles. By giving assurance, BPR gives certainty that the debitors will pay their debt. But still the risk of wanprestasi debitors cannot be avoided. Each BPR has its own way to cope wanprestasi debitors